Analysis of cognitive decline in patients with Huntington's disease using unified Huntington's disease rating scale (2008)
Previous to appearance of motor alterations in Huntington's disease (HD), there can be a discreet cognitive deterioration. During the first decade of evolution of the disease, Mini-Mental State Examination and IQ test may be normal and application of highly sensitive tests become necessary in prediction of anomalies. The cognitive deterioration of HD subjects with less than 10 years evolution was studied using the tests of Verbal Fluency, Symbol Digit Modalities and the entire 3 parts of the Stroop test. A transversal analysis in 61 subjects was employed to seek for correlations of results in these tests and time of evolution of disease and motor deterioration. In the 52 subjects that finished every subsequent evaluation, rates of six-month, yearly and eighteen-month change were estimated. All cognitive tests were significantly related to the motor subscale and time of evolution. Correlation of results in the Stroop test with motor scale produced a Pearson's correlation coefficient of -0.76 for word reading (part A), -0.68 for color naming (B) and -0.64 for interference test (C). Time of evolution was more highly related to the 2 remaining tests. The longitudinal study did not set in evidence any significant change with the exception of the quick reading section of Stroop A test, which showed 7 points deterioration in 18 months. This test turned out to be more sensitive than the other complex tasks for detection of any deterioration. ©INNN, 2008.